The peculiarities of translations of official business plans from english into Russian - Deborah Mensah, Liliya Radikovna Sakaeva, Marat Aidarovich Yahin,; Fatkullina, Flyuza Gabdullinovna (Opción, 2019)
The subject of the present article is the general specificities in the texts of business documentation, specifically business plans and their translations from English into Russian via contextual analysis of the selected texts and systematical method. As a result, in the process of translation the plans, major errors pertain to the interchange of expansions of abbreviations and meanings of polysemies, thus, when one is mistaken for another. In conclusion, the dominant features that are embedded in English business plans are peculiar and make their translations from English into Russian technical.